Back Cover: Cobalt‐Catalyzed Electrophilic Cyanation of Arylzinc Halides with N‐Cyano‐N‐phenyl‐p‐methylbenzenesulfonamide (NCTS) (Adv. Synth. Catal. 16‐17/2015). Issue 16 (23rd October 2015) - Cai, Yingxiao; Qian, Xin; Rérat, Alice; Auffrant, Audrey; Gosmini, Corinne
Abstract : The back cover picture, provided by Corinne Gosmini and co‐workers, illustrates a cobalt‐catalyzed electrophilic cyanation of arylzinc species with N ‐cyano‐ N ‐phenyl‐ p ‐methylbenzenesulfonamide (NCTS). The same cobalt catalyst promoted both the synthesis of the organozinc species and the cross‐coupling reaction. The products, bearing various functional groups, were obtained in moderate to high yields. Details can be found in the communication on pages 3419–3423 (Y. Cai, X. Qian, A. Rérat, A. Auffrant, C. Gosmini, Adv. Synth. Catal. 2015, 357, 3419–3423; DOI:10.1002/adsc.201500245 ).